LEGISLATIVE MECHANISMS FOR COMBATING VIOLENCE AGAINST CHILDREN WITH DISABILITIES IN SELECTED AFRICAN JURISDICTIONS: A CRITICAL APPRAISAL (African Disability Rights Yearbook, 2021)
Children with disabilities in many African countries suffer violence and abuse that take various forms. Human rights treaties, such as the Convention on the Rights of Persons with Disabilities (CRPD) require state parties to take appropriate legislative, policy, administrative and other measures that conform to international standards to protect children with disabilities from violence. At the African regional level, the CRPD is complemented by the African Charter on the Rights and Welfare of the Child. A number of African countries that are party to the CRPD have adopted disability and child protection legislation. For example, Malawi, Zambia Tanzania, Uganda and Kenya have adopted disability specific statutes; while South Africa has enacted child protection legislation. The legislative documents are expected to provide for mechanisms for protecting children with disabilities from violence. The study seeks to analyse the extent to which selected African state parties to the CRPD have put in place legislative mechanisms for protecting children with disabilities from violence as envisaged by international standards, such those under the CRPD. The selected countries are expected to have adopted disability-specific statutes and/or child protection legislation. Accordingly, the study focuses as selected case studies on Malawi, Tanzania, Zambia, South Africa, Kenya, Ghana and Uganda. The study observes that African states need to put in place mechanisms in their child protection and disability-specific legislation that will ensure, amongst others, the identification, investigation and prosecution of all forms of violence and abuse, and the existence of legislative provisions that protect children with disabilities from all forms of violence. Such mechanisms could go a long way towards making the domestic legislative frameworks provide the appropriate mechanisms for combating violence against children with disabilities, as envisaged by the pertinent international standards.
Keywords: Children with disabilities; violence and abuse; Convention on the Rights of Persons with Disabilities; child protection and disability-specific legislation